Achieve CAPM exam success : a concise study guide and desk reference - Altwies, Diane, 1962- (J. Ross Publishing, 2019)
"Used in conjunction with PMI's PMBOK.
Revised edition of Achieve CAPM exam success, [2014].
Includes index.
Keywords: Project management -- Examinations -- Study guides.; Project management -- Examinations, questions, etc.; Project management -- Certification -- Study guides.; elektronické knihy; electronic books